1934
DOI: 10.1021/ac50087a018
|View full text |Cite
|
Sign up to set email alerts
|

Direct determination of chromium and vanadium in steel o-Phenanthroline Ferrous Complex as Indicator

Abstract: THEmost exact methods at the present time for chromium involve the direct titration of the chromic acid, obtained from a persulfate or similar oxidation, with standard ferrous sulfate, The end point may be determined either potentiometrically or with an oxidation-reduction indicator.. If vanadium is present in the steel, as is very often the case, vanadic acid is formed in the oxidation process, and this substance is titrated along with the chromic acid. It is necessary, then, to determine vanadium before the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1935
1935
1965
1965

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The interference of free halogen in the titration was obviated by the use of mercuric oxide. It has also been used in reactions utilizing potassium permanganate (165,297) and potassium dichromate (287). Ferroin is oxidized by dichromate in strongly acid solutions, whereas the reverse reaction can take place in weak acid (174).…”
Section: A As Oxidation-reduction Indicatorsmentioning
confidence: 99%
“…The interference of free halogen in the titration was obviated by the use of mercuric oxide. It has also been used in reactions utilizing potassium permanganate (165,297) and potassium dichromate (287). Ferroin is oxidized by dichromate in strongly acid solutions, whereas the reverse reaction can take place in weak acid (174).…”
Section: A As Oxidation-reduction Indicatorsmentioning
confidence: 99%
“…Oxidation of chromium and vanadium to chromate and vanadate ions may be accomplished by a number of oxidizing agents, such as brómate ion (6, 12), persulfate ion (13), permanganate ion (13), or perchloric acid (10,11,13). Of these reagente, perchloric acid was selected because of the simple and rapid manner in which the oxidation -can be performed.…”
Section: Discussionmentioning
confidence: 99%
“…The indicator has been found to function excellently in simple titrations with solutions of ceric sulfate and potassium dichromate. In a more complicated setting (9,11) it has been found that in a 5 M sulfuric acid solution containing both iron and vanadium, the color change occurs at a potential where iron is completely oxidized, but vanadium is only oxidized to the quadrivalent state. At lower acidities the color change occurs only after both sub- stances are completely oxidized.…”
Section: Phenanthroline-ferrous Ion Indicatormentioning
confidence: 99%